A process evaluation of the improving wisely intervention: a peer-to-peer data intervention to reduce overuse in surgery - Christine Fahim; William E. Bruhn; John G. Albertini; Marty A. Makary (BMC, 2021)
Abstract Background The Improving Wisely intervention is a peer-to-peer audit and feedback intervention to reduce overuse of Mohs Micrographic Surgery (MMS). The objective of this study was to conduct a process evaluation to evaluate Mohs surgeons' perceptions of the implementation quality and perceived impact of the Improving Wisely intervention. Methods Surgeons in the Improving Wisely intervention arm, comprised of members of the American College of Mohs Surgeons (ACMS) who co-led the intervention, were invited to complete surveys and key informant interviews. Participants described perceptions of implementation quality (evaluated via dose, quality of implementation, reach and participant responsiveness), perceived impact of the Improving Wisely intervention (evaluated on a 1-5 Likert and qualitatively), and barriers and facilitators to changing surgeons' clinical practice patterns to reduce Mohs overuse. Results Seven hundred thirty-seven surgeons participated in the survey. 89% were supportive of the intervention. Participants agreed that the intervention would improve patient care and reduce the annual costs of Mohs surgery. Thirty surgeons participated in key informant interviews. 93% were interested in receiving additional data reports in the future. Participants recommended the reports be disseminated annually, that the reports be expanded to include appropriateness data, and that the intervention be extended to non ACMS members. Six themes identifying factors impacting potential MMS overuse were identified. Conclusions Participants were strongly supportive of the intervention. We present the template used to design and implement the Improving Wisely intervention and provide suggestions for specialty societies interested in leading similar quality improvement interventions among their members.